2020
DOI: 10.1001/jamanetworkopen.2020.3951
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Antibiotic Treatment Duration in Children With Pyelonephritis

Abstract: IMPORTANCE National guidelines recommend treating children with pyelonephritis for 7 to 14 days of antibiotic therapy, yet data are lacking to suggest a more precise treatment duration. OBJECTIVE To compare the clinical outcomes of children receiving a short-course vs a prolongedcourse of antibiotic treatment for pyelonephritis. DESIGN, SETTING, AND PARTICIPANTS Retrospective observational study using inverse probability of treatment weighted propensity score analysis of data from 5 hospitals in Maryland betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 22 publications
0
27
0
6
Order By: Relevance
“…Accordingly, different studies investigated the effectiveness of shorter antibiotic regimens in pediatric population. A recent observational study in children reported that 6–9 days of antibiotic treatment is as effective as a longer duration of 10 days in patients affected by febrile UTI [ 79 ]. Outcomes of even shorter courses (1–3 days) are inferior to those of longer courses [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, different studies investigated the effectiveness of shorter antibiotic regimens in pediatric population. A recent observational study in children reported that 6–9 days of antibiotic treatment is as effective as a longer duration of 10 days in patients affected by febrile UTI [ 79 ]. Outcomes of even shorter courses (1–3 days) are inferior to those of longer courses [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the counterfactual scenario of non-infection, AMR in UTI was the fourth most infectious syndrome leading to AMR-related cause of death globally, just behind lower respiratory infections and all related infections in the thorax, bloodstream infections, and peritoneal and intra-abdominal infections [ 4 ]. Additionally, the disease burden of UTI is increasing [ 9 ], and antibiotics are usually recommended for the treatment of UTI [ 14 , 15 , 16 ] and as prophylactics, such as during prostate biopsy [ 17 ] and urological surgery [ 18 ]. Considering these facts, AMR in UTI is a health problem that cannot be ignored, both for the management of urology disease and for global antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluating duration of antibiotic therapy for complicated UTI or Gram‐negative bacteraemia in general population demonstrate noninferiority of short (≤7 days) versus longer treatment (>7 days) [18,20,23]. A recent retrospective observational study examining treatment duration in pyelonephritis in children, showed no difference in odds of treatment failure for patients prescribed a short course (6–9 days) versus a prolonged course (≥10 days) of antibiotics (11.2% vs. 9.4%; odds ratio, 1.22; 95% CI, 0.75–1.98) [24].…”
Section: Discussionmentioning
confidence: 99%